Analisis Pelaksanaan Pendidikan Karakter dalam Pembelajaran Matematika - Chico Aciakatura; Aam Amaliyah; Laily Yuniar Nurazizah; Rahma Azzahrah Putri; Rizkia Dwi Lestari (Jurnal Pendidikan Indonesia, 2022)
Many students are less interested in mathematics, where mathematics is known for its difficulties. But there are also students who enjoy math lessons. The attitudes and traits of students are quite diverse in the classroom with some of the characters they have. As teachers, we must be able to understand and shape the character of students so that they become good students. The purpose of character education is to form the mental and attitudes of students to be more positive. SDN Badak Anom became one of the schools chosen to see the various characters of students in the classroom during mathematics learning. Therefore, students are expected to have the ability of cognitive aspects, psychomotor aspects, and effective aspects. Then apply positive character values. Religious values, discipline values, tolerance values, and responsibility values.